Vaccination as a scheduled demand: a day in the life of users - Deborah Correia Duarte; Selma Maria da Fonseca Viegas; Fernanda Moura Lanza; Valéria Conceição de Oliveira
ABSTRACT Objectives: to understand vaccination as a scheduled demand and access to this demand in a day in the life of health services, from the perspective of users. Methods: holistic-qualitative multiple case study, based on the Quotidian Comprehensive Sociology, with 74 users from four health microregions of the Extended Western Region of Minas Gerais State. Results: scheduling vaccination demand in a day in the life of services is compromised by the fragility in data record, by computerized systems underutilization and by the loss of the immunization tracking card, resulting in missed opportunities of immunization and unnecessary revaccinations. The Primary Health Care team's non-involvement also compromised access to this action. Final Considerations: there is a need for more effort to be dispensed with for the effective use of computerized systems and Permanent Education of professionals in order to take advantage of all the opportunities of orientations and referrals of users to the vaccination room.